2015
DOI: 10.1103/physrevb.92.115443
|View full text |Cite
|
Sign up to set email alerts
|

Observation of two distinct negative trions in tungsten disulfide monolayers

Abstract: Ultrafast pump-probe spectroscopy of two-dimensional tungsten disulfide monolayers (2D-WS 2 ) grown on sapphire substrates revealed two transient absorption spectral peaks that are attributed to distinct negative trions at ~2.02 eV (T 1 ) and ~1.98 eV (T 2 ). The dynamics measurements indicate that trion formation by the probe is enabled by photodoped electrons remaining after trapping of holes from excitons or free electron-hole pairs at defect sites in the crystal or on the substrate. Dynamics of the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 35 publications
10
55
1
Order By: Relevance
“…It is reported that defect sites could dissociate excitons by trapping the holes and leave the electron in the conduction band to bind with photo generated electron‐hole pairs to form negative trion. Further, the pump probe measurements carried out with different laser energy fluence indicates that the observed trion amplitudes are more correlated to the number of trapping sites in comparison to the production of excitons . The similar trionic emission in 2D system is not shown when the monolayer MoS 2 is under biaxial strain with suspended geometry due to absence of substrate effect.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…It is reported that defect sites could dissociate excitons by trapping the holes and leave the electron in the conduction band to bind with photo generated electron‐hole pairs to form negative trion. Further, the pump probe measurements carried out with different laser energy fluence indicates that the observed trion amplitudes are more correlated to the number of trapping sites in comparison to the production of excitons . The similar trionic emission in 2D system is not shown when the monolayer MoS 2 is under biaxial strain with suspended geometry due to absence of substrate effect.…”
Section: Resultsmentioning
confidence: 88%
“…Typically, such negative trions are known to emerge when excess electrons are introduced in photo‐excited excitons . Ultrafast pump probe spectroscopic study clearly revealed the origin of negative trions and its relation with defect sites . Dynamic measurements suggested that trions are formed by photodoping of WS 2 monolayers with residual electrons that are remaining after trapping of holes or free electron‐hole pair at defect sites.…”
Section: Resultsmentioning
confidence: 99%
“…This peculiar evolution originates, as discussed previously in literature [43][44][45][46][47][48], from contribution of two different CX states to the feature observed in absorption-type spectra. The existence of two CX states in 'darkish' materials is a consequence of spin alignment in conduction subbands, which allows an excess electron from either K+ or K− valley to accompany the photo-created electron-hole pair and form a bound CX state.…”
mentioning
confidence: 70%
“…The exceptionally large binding energies of these quasiparticles (i.e. 200-500 meV for excitons and an additional binding energy of 20-40 meV for trions) further promise room temperature valleytronic applications [2,3,[7][8][9][10][11][12][13].High efficiency valley initialization and a long lifetime of valley polarization are preferred in valleytronic applications [14][15][16][17]. Initial experiments based on steadystate photoluminescence have shown the possibility of creating a near-unity valley polarization in MoS2 and WSe2 via exciton resonances [4,18].…”
mentioning
confidence: 99%